Hypotheses and facts about congenital tuberculosis - O. K. Kiselevich; A. A. Ivanova; A. V. Abramchenko; A. N. Yusubova (LLC "Diagnostics and Vaccines", 2023)
Congenital tuberculosis is a rare disease that occurs during intrauterine infection transmission from a mother with an active tuberculosis process to a child. Symptoms and signs may be minimal and non-specific. Unfortunately, it is not always possible to find evidence to confirm congenital children tuberculosis. Early diagnosis and adequate treatment have a significant positive effect on the disease course and outcome. An analysis of 9 articles, published in the domestic literature, describing clinical cases of 11 patients, diagnosed with congenital tuberculosis, the criteria and validity of such a diagnosis were made and considered.